Attitudes toward pregnancy and motherhood and its relationships with prenatal attachment to the fetus: a study with Portuguese pregnant women. - Camarneiro, Ana Paula Forte (2010)
Attitudes toward pregnancy and motherhood and its relationships with prenatal attachment to the fetus: a study with Portuguese pregnant women.